Study of Prescribing Pattern of Antihypertensive Drugs and Evaluation of the Prescription with JNC 8 Guidelines in North Karnataka Hospital - Malpani, Ashok Kumar; Waggi, Manjunath; Panja, Palash; Christien, Thella Monica (Indian Journal of Pharmacy Practice)
Aim: To conduct a prospective observational study on prescribing pattern of antihypertensive drugs and to evaluate the current practice of antihypertensive drug by comparing with JNC-8 guidelines in north Karnataka hospital. Methods: The study was conducted for a period of 6 months with a sample size of 100 of all the in-patient of age ≥ 18 years of hypertension with or without co-morbidities, including pregnant women and lactating mothers. Results: A total of 100 prescriptions were analysed during the six-month study period. 55% were male while 45% were female. 25% patients received monotherapy while majority of the patient’s i.e. 75% were put on multidrug therapy of which, 35% patients on two drug therapy, 32% of patients on three drug therapy and 8% on four drug therapy. The most common drug classes involved in the study were ARBs (17%), BBs (09%) and ACEIs (03%). Our study reveals that without diabetes or CKD (greater than 60 years) 75.60% of patients were compliant with JNC-8 goal (less than 150/90 mmHg) and without diabetes or CKD (less than 60 years) 64.30% of patients were compliant with JNC-8 goal (less than140/90 mmHg). Patients with diabetes and without CKD (all ages) 50% achieved the JNC-8 goal (less than140/90 mmHg) and Patients with CKD or without DM (all ages and races) 60% achieved the JNC-8 goal (less than140/90 mmHg). Conclusion: Calcium channel blockers (Amlodipine) and diuretics (Furosemide) were the drug of choice for hypertensive patients as a single drug and combination drug therapy. As per the JNC 8 guidelines majority of the BP goals were achieved. Our result reveals that antihypertensive medication adherence to JNC 8 guidelines is optimal at the study site.
Keywords: Prescription pattern; Anti-hypertensive; In-patients; JNC-8; Co-Morbidities